2016
DOI: 10.1038/srep22263
|View full text |Cite
|
Sign up to set email alerts
|

Isothiocyanates as effective agents against enterohemorrhagic Escherichia coli: insight to the mode of action

Abstract: Production of Shiga toxins by enterohemorrhagic Escherichia coli (EHEC) which is responsible for the pathogenicity of these strains, is strictly correlated with induction of lambdoid bacteriophages present in the host’s genome, replication of phage DNA and expression of stx genes. Antibiotic treatment of EHEC infection may lead to induction of prophage into a lytic development, thus increasing the risk of severe complications. This, together with the spread of multi-drug resistance, increases the need for nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 51 publications
6
60
0
1
Order By: Relevance
“…The increased expression of sodA gene shows that exposure to the tested essential oils induces oxidative stress in S. mutans. Studies have demonstrated that isothiocynates can cause general stress in E. coli, as evidenced by the increased concentration of general stress regulator molecule guanosine penta/tetraphosphate ((p)ppGpp) [23]. Biofilm formation by oral pathogens is one of the most important traits contributing to their pathogenicity [19,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of sodA gene shows that exposure to the tested essential oils induces oxidative stress in S. mutans. Studies have demonstrated that isothiocynates can cause general stress in E. coli, as evidenced by the increased concentration of general stress regulator molecule guanosine penta/tetraphosphate ((p)ppGpp) [23]. Biofilm formation by oral pathogens is one of the most important traits contributing to their pathogenicity [19,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…However, another related compound, nitroscanate, is widely employed in veterinary medicine to treat roundworm, hookworm and tapeworms [ 33 ]. Currently, the isothiocyanates are researched for activity against intestinal bacteria and cancer [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The strains of E. coli that produce Stx (STEC), such as E. coli O157: H7, have been studied extensively [ 88 ]. ITCs are currently considered as potential therapeutic agents against EHEC infections [ 45 ].…”
Section: Isothiocyanates Antimicrobial Properties Against Human Pamentioning
confidence: 99%
“…Recently, Nowicki et al showed that BITC was more effective than AITC in the inhibition of EHEC E. coli growth [ 45 ]. The study was performed comparing the antibacterial activity of synthetic SFN, AITC, BITC, phenyl ITC (PITC) and isopropyl ITC (IPRITC) against different clinical and laboratory EHEC E. coli strains, including WT ( E. coli MG1655) and Shiga toxin-producing E. coli (O157:H7 E. coli) .…”
Section: Isothiocyanates Antimicrobial Properties Against Human Pamentioning
confidence: 99%